2021
DOI: 10.3390/cells10092381
|View full text |Cite
|
Sign up to set email alerts
|

Control of Neuroinflammation through Radiation-Induced Microglial Changes

Abstract: Microglia, the innate immune cells of the central nervous system, play a pivotal role in the modulation of neuroinflammation. Neuroinflammation has been implicated in many diseases of the CNS, including Alzheimer’s disease and Parkinson’s disease. It is well documented that microglial activation, initiated by a variety of stressors, can trigger a potentially destructive neuroinflammatory response via the release of pro-inflammatory molecules, and reactive oxygen and nitrogen species. However, the potential ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 212 publications
(282 reference statements)
0
17
0
Order By: Relevance
“…Another study showed that application of low dose irradiation strengthens immunity and improves neurodegeneration in the animal models by altering the microglial phenotypes (reviewed by Boyd et al, 2021). Administration of low dose irradiation in microglia reduces microglial activation and enhances anti‐inflammatory cytokine and anti‐oxidant properties, thus enhancing neuroprotection (Boyd et al, 2021). This irradiation strategy to examine the mechanisms underlying the regulation of myelination by microglia remains untested in the CPZ model.…”
Section: Roles Of Astrocytes In Myelin Debris Clearancementioning
confidence: 99%
“…Another study showed that application of low dose irradiation strengthens immunity and improves neurodegeneration in the animal models by altering the microglial phenotypes (reviewed by Boyd et al, 2021). Administration of low dose irradiation in microglia reduces microglial activation and enhances anti‐inflammatory cytokine and anti‐oxidant properties, thus enhancing neuroprotection (Boyd et al, 2021). This irradiation strategy to examine the mechanisms underlying the regulation of myelination by microglia remains untested in the CPZ model.…”
Section: Roles Of Astrocytes In Myelin Debris Clearancementioning
confidence: 99%
“…LDIR may decrease systemic IL-6 levels in mice, including in the brain, through its direct effects on the cells that release cytokines, and indirectly through a reduction of TSPO. It has been demonstrated that the level of TSPO expression positively correlates to the concentration of pro-inflammatory cytokines, including IL-6 ( Karlstetter et al, 2014 ; Betlazar et al, 2016 , 2020 ; Boyd et al, 2021 ). Reversely, increased pro-inflammatory cytokines may trigger an elevated level of TSPO expression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, given the link between the widespread constitutive TSPO expression in these cells, their ability to induce inflammatory responses and oxidative processes after irradiation, and the known involvement of TSPO in these processes, further studies are needed in order to gain insights into TSPO expression in this cell type after irradiation and its potential involvement in radiation-induced endothelial processes. It has been demonstrated that level of TSPO positively correlates with ROS production ( Gatliff et al, 2014 ; Betlazar et al, 2016 , 2020 ; Tu et al, 2016 ; Ilkan and Akar, 2018 ; Boyd et al, 2021 ). ROS and RNS can reversibly modulate TSPO expression ( Loth et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies using NSC/induced pluripotent stem cells (iPSCs) derived from Alzheimer patients with the objective of promoting neurogenesis and ameliorating the progression of the disease ( Wu et al, 2021 ). In one of these studies, for example, they demonstrate that the release of pro-inflammatory cytokines, such as TNF- α, IL-1 β, and IGF-1 by microglia enhance the dopaminergic differentiation of neural stem cells and promote neurogenesis ( Boyd et al, 2021 ; Schmidt et al, 2021 ).…”
Section: Effect Of Microglia On Neural Stem Cell Differentiation In A...mentioning
confidence: 99%